Inorganic/Organic Multilayer Capsule Composition for Improved Functionality and External Triggering - Timin A. S. Aleksandr Sergeevich; Gao H.; Voronin D. V.; Gorin D. A. Dmitry Aleksandrovich; Sukhorukov G. B. Gleb Borisovich (2016, 2016)
Title screen